Course and predictors of upper leg muscle strength over 48 months in subjects with knee osteoarthritis: Data from the osteoarthritis initiative. Issue 2 (June 2020) - de Zwart, A.H.; van der Leeden, M.; Roorda, L.D.; van der Esch, M.; Twisk, J.W.R.; Lems, W.F.; Dekker, J.
Summary: Objectives: Weakness of upper leg muscles has a negative impact on future disease and functional status in subjects with knee osteoarthritis (OA). The aims of the present study were to (i) describe the course of muscle strength over 48 months and (ii) identify baseline predictors for a decline in upper leg muscle strength over time in subjects with knee OA. Methods: Data were obtained from the Osteoarthritis Initiative (OAI) database, a multicenter, observational study of knee OA. Upper leg muscle strength (in N/kg) was measured at baseline, 24 and 48 months. Potential baseline predictors included demographics, OA-specific and health and lifestyle related factors. Linear mixed model analyses were performed. Results: A total of 1390 subjects with knee osteoarthritis were included. A statistically significant decline of muscle strength was found between baseline and 24 months ( B  = −0.186, 95%CI [-0.358, -0.014], p  = 0.03), but not between other time points (24–48 months p  = 0.89, and baseline and 48 months p  = 0.058). Predictors of a decline in muscle strength over time included demographic predictors (older age, being female, higher body mass index (BMI)), one lifestyle predictor (lower dietary protein intake) and one OA-specific predictor (radiographic severity). Conclusions: Muscle strength declined over time in subjects with knee OA. The identified predictors may help clinicians to select and treat subjects with knee OA at risk of a decline in muscle strength.